Rare emergency in children: Priapism and stepwise treatment approach - KARAGÖZLÜ AKGÜL, AHSEN (My University, 2022)
BACKGROUND: Priapism is a rare condition in children and the treatment algorithm is controversial in this age group. Herein, we report eight cases with low-flow priapism and our stepwise treatment approach in light of literature. METHODS: We present a simple stepwise treatment for low-flow priapism including five steps. Step 1: Cold compress and analgesia while evaluation the priapism and its etiology. Step 2: Corporal aspiration and adrenaline infusion in the ward. Step 3: Modified Winter shunt in the same place. Step 4: Ketamine application and caudal block in the operating room. Step 5: Sapheno-cavernous (Grayhack) shunt. Eight cases with low-flow priapism were reviewed retrospectively. Symptoms, duration of tumescence, the interventions, and step that provide detumescence were recorded. RESULTS: The mean age of patients was 8.5 years (1-17 y). The median time of the priapism before admission was 15 h (4-165 h). The etiological factors were sickle cell disease, hemodialysis due to chronic renal failure, and factor V Leiden mutation in three patients. Detumescence was achieved in one patient at Step 2, in two patients at Steps 3, 4, and 5, respectively. Rigidity of cavernous body was observed in one patient in long-term follow-up. CONCLUSION: Low-flow priapism is a urological emergency that may cause erectile dysfunction. Treatment options should be selected according to a protocol that prevents time loss and avoids more invasive treatment in unnecessary situations. Our algorithm with simple nature and its steps from less invasive to more invasive procedures may be an alternative for the treatment of low-flow priapism.
Keywords: Tıp; Cerrahi Tıp Bilimleri; Acil Tıp; Sağlık Bilimleri; Medicine; Surgery Medicine Sciences; Emergency Medicine; Health Sciences; ACİL TIP; Klinik Tıp; Klinik Tıp (MED); EMERGENCY MEDICINE; CLINICAL MEDICINE; Clinical Medicine (MED); Acil Tıp Hizmetleri; Emergency Medical Services; Child; hemodialysis; priapism; sapheno-cavernous shunt; stepwise treatment; RECURRENT ISCHEMIC PRIAPISM; LOW-FLOW PRIAPISM; DYSFUNCTION; MANAGEMENT; SHUNT